Pengaruh Penggunaan Bahasa Daerah Dalam Pergaulan Sehari-Hari Mahasiswa UNDIKMA Terhadap Keterampilan Berbahasa Indonesia - Supriadin, Supriadin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
The purpose of this study was to determine the effect of the use of regional languages by students on Indonesian language abilities and skills. This research is quantitative research, with the research method used in the form of a survey method. The use of random sampling techniques, in order to make it easier to get a wider range of respondents. The subjects of this study were UNDIKMA students. The results of this study indicate that regional languages act as a means of communication between the same tribes. Regional languages are still widely used by students in communicating in non-formal and formal settings such as during the lecture process. In conclusion, the use of regional languages by students has quite an effect on Indonesian language skills and abilities.